Aminothiolation of alkenes with azoles and Bunte salts - Ouyang, Bingqing; Chai, Xing; Li, Zhe; Zhang, Chunling; Liu, Xingmei (Frontiers in Chemistry, 2024)
We have developed an intermolecular aminothiolation of simple olefins using Bunte salt as a thiolating agent. This protocol produces thiyl free radicals under PIDA oxidation conditions, eliminating the need for transition-metal catalysts. The method has a wide range of substrate applicability and is suitable for large-scale preparation and late-stage modification of drug molecules.